De la ilustración al diseño gráfico en Billiken - Alberdi, Isabel (2021)
The following study investigates the graphic as production of meaning, in particular how Graphic Design operates in its argumentative dimension (Kinross 1989, Buchanan 1985 and Tapia 2004) on the covers of Billiken magazine.\nThe study of covers resulted as a preferential space for argumentation in a journal (Traversa 2009, Cingolani 2009).\nThe corpus with 92 copies, from January 1971 to October 1972, encompasses a change in the form that coincides with computerization in the process of assembling magazines at the local level.\nThe designed object was taken as a system of articulated visual elements (Mazzeo 2017) which allowed to pull apart and classify the graphic resources for analysis.\nA passage from illustration to logics typical of Graphic Design was verified, coupled with changes in both the technical sphere (Castoriadis 2003-2004) and the communication sphere.\nIssues such as the function of the covers and therefore the resources present; the coordination of arguments in communication; and criteria in planning decisions; took center stage in the analysis of the changes in the formal.